That's gross! - Boyer, Crispin (Washington, D.C. : National Geographic, 2012)
Contains descriptions of a wealth of disgusting, gross, and repulsive things, grouped in the categories of the human body, nature, animals, and food.
8.4
3-6
3-6
NC1130L
Keywords: Curiosities and wonders -- Juvenile literature; Animals -- Miscellanea -- Juvenile literature; Food -- Miscellanea -- Juvenile literature; Human body -- Miscellanea -- Juvenile literature; Curiosities and wonders; Animals -- Miscellanea; Food -- Miscellanea; Human body -- Miscellanea; Curiosities and wonders; Animals -- Miscellanea; Food -- Miscellanea; Human body -- Miscellanea